Reduction of stresses and mass of an engine rubber mount subject to mechanical vibrations - Dávalos, Omar (Strojniški vestnik, 2021)
A rubber engine mount (EM) is a mechanical coupling between the engine and the chassis, and its main function is to diminish, in the chassis, the amplitude of vibrations caused for the engine operation. Such vibrations cause discomfort for vehicle passengers and reduce the EM lifetime. To increase the comfort of vehicle passengers and the lifetime of the EM, this paper presents an EM optimization by means of reducing three main criteria: the EM mass, the displacements transmitted to the chassis, and the mechanical stress in the EM rubber core. For carrying out the EM optimization, the optimum global determination by linking and interchanging kindred evaluators (GODLIKE), assisted by artificial neural networks (ANN) and finite element method (FEM), was used. Because of the optimization process, a reduction greater than 10 % was achieved in the three criteria in comparison with a baseline design. The frequency responses were compared and showed that although the optimization was carried out for the range of 5 Hz to 30 Hz the trend of reduced responses continues beyond this range. These results increased the comfort of vehicle passengers and the lifetime of the EM; in addition, the reduction of mass diminishes its production costs.
Keywords: ANN; določitev globalnega optimuma; FEM; global optimum determination; MKE; multi-objective optimization; nosilec motorja; umetna nevronska mreža; večciljna optimizacija; vehicle engine mount; vibracije